A rare subtype of lynch syndrome familial with co-mutation of EpCAM c.344T>C, MSH2 c.2744A>G, PMS2 c.1408C>T and APC c.5465T>A, case report and literature review - Lu, Guiyu; Pan, Ting; Deng, Cuidong; Wan, Xiaoqian; Wang, Zihan; Hu, Tengyue; Cheng, Xianshuo; Dong, Jian (Frontiers in Genetics, 2025)
BackgroundLynch syndrome (LS) is an autosomal dominant disorder caused by germline mutations in mismatch repair (MMR) genes or EpCAM, leading to various cancers, particularly colorectal cancer (CRC). EpCAM mutations account for approximately 1%–3% of LS cases, while co-mutations involving EpCAM and MSH2 are exceedingly rare. To date, co-mutations of EpCAM, MSH2 and PMS2 have not been reported in the literature.Case PresentationThis case reports a 25-year-old male diagnosed with adenocarcinoma of the ascending colon. His family history revealed eight cancer cases among 30 relatives across five generations, consistent with LS. Immunohistochemistry (IHC) of the tumor showed loss of EpCAM, MSH2 and MSH6 protein expression. Genetic testing of the proband’s tumor identified a novel large deletion affecting EpCAM exons 8-9 and MSH2 exons 1–16, likely pathogenic mutations disrupting MMR gene function. Whole-exome sequencing (WES) of peripheral blood from six family members, including the proband and his son, revealed co-mutations of EpCAM (c.344T>C), MSH2 (c.2744A>G), PMS2 (c.1408 C>T) and APC (c.5465T>A). Although public databases suggested these variants are benign or of uncertain significance (VUS), several in silico prediction tools and prior literature suggest potential pathogenicity. Notably, WES of the proband’s son’s peripheral blood also detected the same large deletions in EpCAM and MSH2, implying the presence of germline mosaicism and a possibly heightened early-onset cancer risk.ConclusionThis rare subtype of LS emphasizes the need for comprehensive genetic screening and may inform future strategies for early detection and management in LS families. Further studies are required to confirm these findings.